62‐8: Invited Paper: High Color Gamut QDot™ LCD Displays with Perovskite Quantum Dots: Devices Architecture, Performance and Reliability. Issue 1 (28th June 2021) - Sinatra, Lutfan; Lutfullin, Marat; Lentijo-Mozo, Sergio; Bakr, Osman M.
Abstract : Perovskite Quantum Dots (QDs) promise to deliver over 90% of Rec2020 color representation, the highest for RoHS compliant LCD displays. In this study, we strive to demonstrate the performance of LCD displays using QDot™ green emitting Perovskite QDs with various backlight architectures. Using different blue and red light sources, we fabricated four types of LCD display, which showed contrasting Rec2020 color gamut from 80 to 86% and brightness from 1000 to 2000 nits. With these impressive metrics, Perovskite Quantum Dots paves the way for mass adoption of the technology in the display field.